1996
DOI: 10.1021/jf960115f
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Sensory Characterization of Volatile Flavor Compounds in Sesame Seed Oil

Abstract: Voltile flavor compounds in sesame seed oil were investigated. Commercially processed sesame seed oil was steam distilled under reduced pressure, and volatiles from the distillate were separated by an adsorptive column method. Among 171 individual peaks detected, 134 peaks were definitely or tentatively identified by analysis of mass spectra and modified Kovats indices. To elucidate the compounds directly contributing to the characteristic flavor, the odor concentrate was fractionated by silica gel thin-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 6 publications
8
65
0
2
Order By: Relevance
“…En effet, la faible température de torréfaction de la productrice 1 a conduit au rendement d'extraction le plus faible alors que la forte température de torréfaction utilisée par la productrice 3 a conduit au rendement de production le plus élevé. Shimoda et al (1996) et Krist et al (2006) ont rapporté que la torréfaction des amandes de karité est une pratique qui permet d'améliorer le rendement et les caractéristiques sensorielles du beurre. Cependant, le chauffage insuffisant ou à faible température peut réduire le rendement d'extraction (Krysiak et Motyl-Patelska, 2005).…”
Section: Rendement Des Opérations Unitairesunclassified
“…En effet, la faible température de torréfaction de la productrice 1 a conduit au rendement d'extraction le plus faible alors que la forte température de torréfaction utilisée par la productrice 3 a conduit au rendement de production le plus élevé. Shimoda et al (1996) et Krist et al (2006) ont rapporté que la torréfaction des amandes de karité est une pratique qui permet d'améliorer le rendement et les caractéristiques sensorielles du beurre. Cependant, le chauffage insuffisant ou à faible température peut réduire le rendement d'extraction (Krysiak et Motyl-Patelska, 2005).…”
Section: Rendement Des Opérations Unitairesunclassified
“…The detection and the discrimination of odor character were performed by directly sniffing at the odor sniffing port with the GC-Olfactometry (GC-O) technique (9,10,11,12). Also, the odor intensity was evaluated by the Flavor Dilution (FD) factor.…”
Section: Gc-o Analysismentioning
confidence: 99%
“…Sesame oil, prepared from roasted sesame seeds, has a distinctive flavor and long shelflife (Kikugawa et al, 1983;Manley et al, 1974). Several studies have been reported on the flavor components of sesame oil (Yamanishi et aI., 1960(Yamanishi et aI., , 1967Yoko et al, 1969, Yen, 1990, Shimoda et al, 1996, 1997. The condition of roasting process is the key step in manufacturing sesame oil, significantly influencing the color and flavor quality of sesame oil.…”
Section: Influence Of Seed Roasting Process On the Changes In Volatilmentioning
confidence: 99%
“…Volatiles were isolated from the dispersion by a combination of steam distillation under reduced pressure (90 mm Hg) and column concentration (Shimoda et al, 1996(Shimoda et al, ,1997Shiratsuchi et al, 1993). Adsorbed volatiles were eluted with 60 mL of diethyl ether, and 10 ilL of 1 % 3-phenyl-l-propanol in diethyl ether was added as an internal standard.…”
Section: Isolation Of Volatile Flavor Compoundsmentioning
confidence: 99%
See 1 more Smart Citation